¿Se puede prescindir de la Ciencia de la Lógica en la Filosofía del Derecho de Hegel? - Giusti, Miguel (2013)
Can Hegel's Philosophy of Right do without the Science of Logic?”. The question posed by this paper’s title refers to the attempts of some contemporary authors, amongst them Axel Honneth, to update the central theses of Hegel’s Philosophy of Right, though precisely (and deliberately) doing so without its alleged dependence on the Science of Logic. On account of several methodological and hermeneutical reasons, it is not easy to answer this question. It is well known that Hegel emphatically asserts that both works and philosophical projects depend on each other, but there is no consensus amongst specialists on how much the Logic actually influences the Philosophy of Right and in what way it does so. On the other hand, clearly any social philosophy needs a logical theory in a broad sense, whether it may be Hegelian or not. This is even more so if the aim is to update the Hegelian construction implicit in the notion of freedom. In any case, the discussion seems to bring forth the paradox of asserting both the current relevance and the obsolescence of the Hegelian notion of freedom.